Respuesta :

rb5994

3x-6x<-1-5= -3x<-6=x>2

The solution will be x>2.

What is inequality?

Mathematically Inequality shows the relationship between two expression like greater than, greater than equals to, lesser than, lesser than equals to.

To solve this inequality,

3x + 5 < 6x – 1

⇒3x+5+1<6x-1+1                 (add 1 on both side)        

⇒3x+6<6x

⇒3x+6-3x<6x-3x                (substract 3x on both side)

⇒6<3x

⇒6/3<3x/3                          (divide 3 on both side)

⇒2<x

⇒x>2

Therefore, the solution will be x>2.

Learn more about inequality

Here : https://brainly.com/question/11613554

#SPJ2

ACCESS MORE